Supernova's neutrino detection at the Jiangmen Underground Neutrino Observatory. Issue 1 (1st February 2023) - Lombardo, C.; ,
Abstract: The Jiangmen Underground Neutrino Observatory (JUNO) will be the largest ever built liquid scintillator detector for neutrino physics. JUNO is a 20 kton liquid scintillator detector, equipped with 20012 large PMTs and 25600 small PMTs. It will be sensitive to various neutrino sources and will give a unique contribution to the observation of the all-flavor neutrino flux from a Galactic core collapse supernova (CCSN). JUNO can detects neutrinos emitted by the next CCSN neutrinos through several interactions, among which inverse beta decay, elastic scattering on electron and proton can providing information of energy spectra of all flavors. Furthermore, JUNO will be able to provide an alert during the pre-SN phase. In this manuscript, the observatory detectors and its capability to detect CCSN neutrinos will be presented.